Acupuncture to Increase Animal Appetite: A Systematic Review - Zahrudin, Elham; Khairunnisa, Hanifa Khansa; Afandik, Nadya Ashila; Herdiansyah, Akbar Dimas; Çalışkan, Hakan; Firdausy, Lintang Winantya (Jurnal Medik Veteriner, 2025)
Appetite loss in animals can lead to significant health and productivity issues, particularly in agricultural systems. While pharmacological stimulants are commonly used, concerns regarding drug residues and antimicrobial resistance have led to an increased interest in natural alternatives such as acupuncture. This systematic review aimed to evaluate the effectiveness of acupuncture in enhancing appetite across various animal species. Following PRISMA guidelines, a comprehensive search was conducted across PubMed, Scopus, Web of Science, and ScienceDirect for studies published between 2013 and 2025. Inclusion criteria focused on original research investigating acupuncture effects on feed intake, appetite behavior, or appetite-related biomarkers in animals. Data from 27 eligible studies were extracted and analyzed for species, acupoints, techniques, outcomes, and quality. The majority of studies (81.5%) demonstrated a significant increase in appetite or feed intake following acupuncture, particularly electroacupuncture targeting acupoints ST36 and SP6. Hormonal analysis in several studies revealed increased ghrelin and neuropeptide Y levels and reduced cortisol concentrations. Poultry and swine responded most rapidly to treatment, while ruminants showed gradual but sustained improvements. The overall risk of bias was low to moderate. Acupuncture is a promising non-pharmacological intervention to improve animal appetite through neuroendocrine regulation. It offers a sustainable, welfare-friendly approach compatible with organic and drug-free production systems. However, further standardized, large-scale studies are needed to establish clinical protocols and confirm long-term efficacy.